(3cJGH GdCTcGds
(3ChdgG (B:s
(3faQV KdGKI CYOGO eJfGSHI fSHI C Edi M GdChSW s
(3BNQgG (B:s
(3aCfG fVQH h GdeYdhe ai M GdeYdhe hfbSeg Ydi H GdeYdhe jNQL W GdeYdhe JeJ GdCTcGd hGdMeO ddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3eMeO Hf SQjGb Hf LhHGf GdeQGZis
Keywords: (3GdQjGVjGJs